1982
DOI: 10.3354/meps009101
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Investigations of Surface Microlayers, Water Column, Ice and Sediment in the Arctic Ocean

Abstract: A microbiological study was conducted in the area north and northeast of Svalbard, Arctic Ocean. Samples were taken in surface microlayers, ice, water column (down to 300 m) and sediment (maximum depth 3920 m). ATP-content in the upper 100 m was between 8 and 80 ng I-'; total bacterial numbers varied between 0.4 and 4.4 105 ml-l. Ice-samples contained high amounts of ATP (max. 120 ng I-'). Bacteria accumulated at the air-sea interface (surface microlayers) at concentrations 130 to 300 times those in subsurface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…A recent paper by Cho et al (1996) found that urea production by bacteria could account for 35 to 91 % of the estimated nitrogen demand by phytoplankton in the Southern California Bight, USA; such production was also 2 orders of magnitude greater than the rate of urea degradation by bacteria in the same environment. So far as we are aware, the production of urea by bacteria in ice-related environments has not been studied, but there is ample evidence that bacteria can survive and grow in or in near contact with ice (Dahlback et al 1982, Smith et al 1989, Kottmeier & Sullivan 1990, Mordy et a1.1995. but not at a sufficiently rapid rate to seriously influence our frozen nutrient samples (Grossman & Gleitz 1993).…”
Section: 5mentioning
confidence: 99%
“…A recent paper by Cho et al (1996) found that urea production by bacteria could account for 35 to 91 % of the estimated nitrogen demand by phytoplankton in the Southern California Bight, USA; such production was also 2 orders of magnitude greater than the rate of urea degradation by bacteria in the same environment. So far as we are aware, the production of urea by bacteria in ice-related environments has not been studied, but there is ample evidence that bacteria can survive and grow in or in near contact with ice (Dahlback et al 1982, Smith et al 1989, Kottmeier & Sullivan 1990, Mordy et a1.1995. but not at a sufficiently rapid rate to seriously influence our frozen nutrient samples (Grossman & Gleitz 1993).…”
Section: 5mentioning
confidence: 99%
“…Nutrient levels in annual or first-year sea ice generally parallel salinity distributions throughout most of the ice sheet [Grainger, 1977] Table 2 are based on seasonal data for Resolute Bay from the spring of 1983 or 1984. Comparable values for amphipods and nematodes [Carey, 1985], for ciliates [Grainget and Hsiao, 1982], and bacteria [Dahlback et al, 1982' Grossi et al, 1984 have been repor.ted for similar sea ice communities. We consider only the dominant forms of heterotrophs.…”
Section: Desalination Nutrient Supplymentioning
confidence: 99%
“…In this study, mostly first-year ice floes strongly affected by melting were investigated. Abundances of sea-ice bacteria were in the range of published data for the Barents Sea and the Laptev Sea (Dahlbäck et al 1982;Gradinger and Zhang 1997). The vertical distribution of sea-ice bacteria followed bulk salinity that gradually increased from top to bottom in most ice cores.…”
Section: Organic Matter Distribution and Heterotrophic Bacterial Actimentioning
confidence: 58%
“…Based on satellite observations, it has been estimated that Arctic net primary production increased by 30% between 1998 and 2012 mainly due to reduced ice concentration and longer growing seasons (Arrigo and van Dijken 2015). For the Eurasian Basin, estimates derived from the 14 C-bicarbonate method (Steemann Nielsen 1952) combined with an irradiance-based model revealed a doubling of net primary production between 1982(Fernández-Méndez et al 2015. Little is known about the effects of ongoing environmental changes on the heterotrophic recycling of organic matter in the Arctic Ocean.…”
mentioning
confidence: 99%